Serum Immunoglobulin-G Level In Children With Respiratory Tract Infection - Akhter, Salma; Begum, Noorzahan (Journal of Bangladesh Society of Physiologist, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction- Acute respiratory tract infection is one of the important cause of death in children under 5 years of age in developing countries. Perhaps they have a reduced immunologic capacity. Objectives- To observe the serum IgG level in the children suffering from respiratory tract infection in order to evaluate the immunity status in this group of population. Study design- This cross-sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbagh, Dhaka from January to December 2001.Total 60 children age ranged from 3-5 years of both sexes were included in this study. Of them 30 apparently healthy children were considered as control and 30 children suffering from respiratory tract infection were considered as study group and further subdivided into 2 subgroups on the basis of presence of type of RTI. Group B1 consisted of 15 children with acute attack and B2 with recurrent attack. Method: Serum imunoglobulin G level of all the children were measured by Radial Immuno diffusion Method. Datawere analyzed by unpaired t test. Result- The mean (±SE) of serum IgG levels were 10.17±0.37, 10.05± 0.40 and 10.01± 0.52 g/l in control group and two study subgroups respectively. The data were almost similar in all the groups and no statistically significant (p > 0.05) differences were observed. Conclusion - This study reveals that there was no involvement of the IgG status with acute and recurrent respiratory tract infections in the children. Keywords - Children, Respiratory tract infection, Immunoglobulin G. doi: 10.3329/jbsp.v3i0.1798 J Bangladesh Soc Physiol.2008 Dec;(3):55-57.